2010
DOI: 10.1007/s12350-010-9213-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the influence of age and gender on the relationships between infarct size, infarct severity, and left ventricular ejection fraction in patients successfully treated with primary percutaneous coronary intervention

Abstract: Background. Female sex and advanced age have adverse prognostic meaning in acute myocardial infarction. Whether gender and/or age influence the relationship between infarct size, infarct severity, and left ventricular ejection fraction (LVEF) is unclear.Methods. We examined 460 patients (359 men) with acute myocardial infarction submitted to successful primary percutaneous coronary intervention. Infarct size, infarct severity, and LVEF were evaluated with perfusion gated SPECT at one month of index infarction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Both Gevaert et al and Sederholm Lawesson et al showed that female gender was independently associated with renal dysfunction at admission in PCI‐treated patients. Furthermore, Sciagra et al showed that among 460 patients with acute myocardial infarction, there was a significant gender‐related difference with left ventricular ejection fraction decreasing more sharply in females than in males. The higher rate of complications can also be explained by the higher baseline risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Both Gevaert et al and Sederholm Lawesson et al showed that female gender was independently associated with renal dysfunction at admission in PCI‐treated patients. Furthermore, Sciagra et al showed that among 460 patients with acute myocardial infarction, there was a significant gender‐related difference with left ventricular ejection fraction decreasing more sharply in females than in males. The higher rate of complications can also be explained by the higher baseline risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study was retrospective and involved a small number of patients with perfusion abnormalities. Second, several studies evaluated the impact of age and gender on the relationship between LVEF and clinical outcomes [35,36]. We did not take such a point into account in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…And myocardial perfusion reserve even had stronger correlation with LVEF than infarct size. 24 Even in a previous clinical trial, there was a negative linear relation between infarct size and LVEF in patients with moderate to large infarcts. 25 Taken together, it is necessary to estimate the ventricular function in addition to infarct size when evaluating myocardial ischemia-reperfusion injury.…”
Section: Myocardial Infarction Sizementioning
confidence: 90%